Al-Maskoot by the Imam Al-Sarkhasi (peace be upon him) - Manshood , Omar (Islamic Sciences Journal, 2023)
The importance of the subject lies into the matters dealt with in the current study . The subject of the current study ((al-Maskoot ) by the Imam ( al-Sarkhasi ) includes two things ,i.e. its core meaning is concerned with the accurate rules which is (al-Maskoot) for having the fundamentalists and jurisprudents kept silent and not giving any definition about it despite their intensive indications . Imam ( Sarkhasi) is a fundamentalist and he has not given a definition about this term , but he has refereed to its concept and its content in his volumes (al-Maskoot) and ( The concept of Statement) and other conceptshe has referred to . applications of this concept in various issues. The term ( al-Maskoot) has not been given a definition just like other terms and it has been recently known as a matter having not opposed by the legislation and its judgment is indicated with the rule of originality.